The role of perceived benefits in formation of intention to use Islamic crowdfunding platform among small and medium enterprises in Malaysia - Md Husin, Maizaitulaidawati; Haron, Razali; Aziz, Shahab (Academia Industry Networks, 2019)
Are economic benefit, convenience and transaction process important in influencing perceived benefits of the Islamic crowdfunding platform? How do perceived benefits affect user’s intention to use the platform? To answer these questions, this paper i) developed a theoretical framework describing the perceived benefit-intention of a potential Islamic crowdfunding platform user, ii) conducted a self-administered and structured online survey targeting small and medium enterprises (SMEs) in Selangor, Malaysia using the purposive sampling technique, iii) tested the proposed model using a Structural Equation Modelling technique via SmartPLS, and iii) considered the implications of the model. This paper found that economic benefit has a positive and significant relationship with perceived benefits. Transaction process on the other hand has a negative and significant relationship with perceived benefits, while perceived benefits was found to have a significant relationship with intention. On the other hand, convenience was found to have insignificant relationship with perceived benefits. Significant and contribution of this paper is further discussed.